1995
DOI: 10.1042/bst023303s
|View full text |Cite
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids (PUFA) modulate the expression of functionally associated molecules on human monocytes

Abstract: N-3 polyunsaturated fatty acid (PUFA)-rich diets are associated with suppression of the immune system and there is growing interest in the potential use of dietary fish oil [rich in the n-3 PUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] supplementation in the treatment of disorders involving an overreactive immune response, such as rheumatoid arthritis [see 1 for review]. Although it has been shown that n-3 PUFAs can inhibit the proliferation of stimulated lymphocytes [see 2 for review], th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…After 24 weeks, a fall in the proportion of peripheral blood CD4 + cells and an increase in CD8 + cells was observed (Meydani et al 1993). Supplementation with n-3 PUFA depressed immune reactivity in volunteers by suppressing the expression of monocyte surface molecules associated with their antigenpresenting function (Hughes et al 1995).…”
Section: Fish Oilsmentioning
confidence: 99%
“…After 24 weeks, a fall in the proportion of peripheral blood CD4 + cells and an increase in CD8 + cells was observed (Meydani et al 1993). Supplementation with n-3 PUFA depressed immune reactivity in volunteers by suppressing the expression of monocyte surface molecules associated with their antigenpresenting function (Hughes et al 1995).…”
Section: Fish Oilsmentioning
confidence: 99%
“…The major PUFA present in fish oil, eicosapentaenoic acid (EPA), can inhibit antigen‐presenting cell function in mice, and we have shown that, after a three‐week period of dietary fish oil supplementation (3g/day), monocytes from healthy human volunteers exhibited a significant reduction in the expression of the cell surface molecules involved in this process[4]. At the Institute of Food Research we have also shown that EPA can inhibit the expression of these surface molecules on human monocytes in vitro .…”
Section: Fish Oil and Immune Cell Functionmentioning
confidence: 99%
“…n3-PUFAs can regulate the transcription and expression of inflammatory mediators such as cytokines, chemokines and adhesion molecules in cardiomyocytes, fibroblasts, endothelial cells, and monocyte-macrophages ( 101 104 ). Anti-inflammatory effect of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and their biologically active metabolites (D and E Resolvins - mediators derived from omega-3 fatty acids, primarily EPA and DHA that block the production of proinflammatory mediators and regulate leukocyte trafficking to inflammatory sites) can be mediated through one of the mechanisms capable of reducing inflammation of RAW-264.7 cells and of primary intraperitoneal macrophages ( 105 ).…”
Section: Nutrients and Inflammation: Role Of The Diet And Polyunsaturmentioning
confidence: 99%